Pengembangan Aplikasi Statistik untuk Manajemen Data dan Analisis Hipotesis - Putri Nurvadilla Syah Panjaitan; Iskandar Mandika Sebayang; Fahmi Alfarizi Bukit; M Dimas Afandi; Mhd.Hafiz Ibrahim lubis; Kurnia Nabila Hasibuan; Mardhiah Mawaddah; Diego alghifari simamora; Mia Audina; Selamat Indra; Ahmad fawwaz rajfan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study is to find out how to use statistics to assist in the principal's decision-making in the field of management for educator development. Statistics plays an important role in the development of science, one of which is in education. Educational statistics can be used to process data with the SPSS and Microsoft Excel application programs. So far, applications have been widely used by students in analyzing data to help develop the profession and quality of educators. This study will provide an example of implementing the application to determine the determining factors among several factors that affect performance. The research method used is Research and Development (R&D) with a Waterfall model approach, which includes the stages of needs analysis, design, implementation, testing, and evaluation. Testing is carried out through expert validation, system functionality testing, and user testing. The test results show that this application has a high level of feasibility based on expert validation, and is considered easy to use and accurate in producing analysis by users.